Analisis Kendala Pengadaan Obat Program Rujuk Balik (PRB) di Fasilitas Kesehatan Tingkat Pertama (Studi Kasus Pada Puskesmas BLUD di Kabupaten Indragiri Hilir) : Analisis Kendala Pengadaan Obat Program Rujuk Balik (PRB) di Fasilitas Kesehatan Tingkat Pertama (Studi Kasus Pada Puskesmas BLUD di Kabupaten Indragiri Hilir) - elinda rahayu; Fitriyah Kusumawati (BPJS Kesehatan, 2023)
Program Rujuk Balik (PRB) is a health service program for Jaminan Kesehatan Nasional (JKN) participants with chronic illnesses in stable condition and still require long-term care. PRB has not run optimally; one of the reasons is related to drugs. The aim of the study was to examine the procurement of drugs for PRB patients at the Public health center (Puskesmas). This research in Indragiri Hilir Regency, Riau Province, in 2022. Data collection was carried out by Focused Group Discussions (FGD) and in-depth interviews with the Leaders and Managers of the pharmacy department at 5 Puskesmas and the Pharmaceuticals and medical devices (Farmalkes) Sub-coordinator at the Public Health Office Indragiri Hilir. The results showed that Puskesmas did not procure PRB drugs because the drugs were provided by pharmacies in collaboration with BPJS Kesehatan, and they didn’t know how to procure drugs through e-purchasing. Constraints in procuring PRB drugs at the Puskesmas: a). The need for PRB drugs for each Puskesmas were different; b). Puskesmas do not yet have competent human resources; c). Not all Puskesmas have pharmacists; d). The budget plan for drug expenditure at the Puskesmas doesn’t match with payment period for PRB drug claims. Socialization and assistance of drug procurement by e-purchasing at the Puskesmas level, periodic evaluations, and increasing of the Health Service Office must be carried out. The drug procurement system needs to be simplified, and Puskesmas also requires adequate human resources in number and competence for the procurement.